1998
DOI: 10.1074/jbc.273.43.28360
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's Peptide Aβ1–42 Binds to Two β-Sheets of α1-Antichymotrypsin and Transforms It from Inhibitor to Substrate

Abstract: The serpin ␣ 1 -antichymotrypsin is a major component of brain amyloid plaques in Alzheimer's disease. In vitro ␣ 1 -antichymotrypsin interacts with the Alzheimer's amyloid peptide A␤ 1-42 and stimulates both formation and disruption of neurotoxic A␤ 1-42 fibrils in a concentration-dependent manner. We have constructed a new hybrid model of the complex between A␤ 1-42 and ␣ 1 -antichymotrypsin in which both amino and carboxyl sequences of A␤ 1-42 insert into two different ␤-sheets of ␣ 1 -antichymotrypsin. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
36
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 31 publications
2
36
0
Order By: Relevance
“…We have shown that ACT binds A␤ to form an SDS-stable complex rendering ACT a weaker inhibitor of chymotrypsin (48). Recently the binding of A␤ to ACT was described in structural detail (49). Binding of ACT to A␤ could render A␤ a poorer substrate for degradation.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that ACT binds A␤ to form an SDS-stable complex rendering ACT a weaker inhibitor of chymotrypsin (48). Recently the binding of A␤ to ACT was described in structural detail (49). Binding of ACT to A␤ could render A␤ a poorer substrate for degradation.…”
Section: Discussionmentioning
confidence: 99%
“…The human ACT gene shares the highest sequence homology with the family of murine Spi-2 protease inhibitors (Inglis and Hill, 1991). However, the reactive center loop of these protease inhibitors, which is the likely A␤ peptide interacting region in the human ACT protein (Potter et al, 1992;Janciauskiene et al, 1996Janciauskiene et al, , 1998, is hypervariable and differs substantially from that of the human ACT protein (Hill and Hastie, 1987). Here we report on a new transgenic mouse and on experiments pursued to determine the function of ACT as an amyloid promoter in vivo.…”
mentioning
confidence: 99%
“…In vitro studies have demonstrated that ACT and ApoE promote the assembly of the A␤ 1-42 peptide into amyloid filaments (Ma et al, 1994(Ma et al, , 1996Sanan et al, 1994;Wisniewski et al, 1994;Janciauskiene et al, 1996Janciauskiene et al, , 1998. However, using the A␤ 1-40 peptide or an equimolar ratio, ApoE and ACT have also been reported to inhibit A␤ filament formation (Fraser et al, 1993;Eriksson et al, 1995;Evans et al, 1995).…”
mentioning
confidence: 99%
“…strated by the finding of raised levels in brain homogenates from affected individuals 6 ; the finding that it is tightly associated with virtually all ␤-amyloid plaques 7 ; and the demonstration that it interacts with, 8,9 and affects the clearance of, A␤ . [10][11][12][13][14] Moreover elevated levels of plasma and CSF ␣ 1 -antichymotrypsin correlate with cognitive decline in elderly nondemented persons and those with AD.…”
mentioning
confidence: 99%